The Implementation Of Boundary Marks Obligations For Land Ownership Rights Based On Pp No 24 Of 1997 As One Of The Facilities Of Legal Certainty Provision In Kudus - Lucky Wahyu Andriyanto; Kustriyo Kustriyo; Amin Purnawan (Jurnal Akta, 2018)
In order to ensure certainty of land rights and certainty, the UUPA has outlined the necessity to carry out land registration throughout Indonesia. One of the land registration activities is the land measurement with the obligation to install boundary line markers for land owners, in order to avoid land disputes in the later days. The approach method was done by social jurisdiction by using primary data and secondary data. The data were gained through interview and library method, then they were analyzed qualitatively. The results of the discussion indicate that (1) the implementation of the obligation to install the land boundary line  is done by the holder of the land right with the approval of the neighbors land holder who is bordered by the village apparatus or device and the legal consequences can cause the land dispute (2) provide legal certainty to the holder of the land rights (3) The obstacles faced are the absence of the holder of the land right and the need for the presence of the right holder in accordance with the timing of the installation of the land boundary.Keywords: Land Registration; Legal Certainty; Installation of Land Border Marks